On Digital Rupiah And Islamic Economy: A Comparative Analysis And Ethics - Firdaus, Qusthan (Al-bank: Journal of Islamic Banking and Finance, 2024)
This study aims to explore the meaning of and to conduct an ethical assessment towards Digital Rupiah to Islamic economy by exploring the thoughts of Baqir Sadr and Henry Sidgwick. This research is about an ethics of Digital Rupiah, and it would like to investigate two problems. First, do these retail and wholesale versions of Central Bank Digital Currency (CBDC) or the so called Digital Rupiah cause any harm to some principles in Islamic economy especially the one in SadrÔÇÖs thought? Second, is utilitarianism, in the sense of Henry SidgwickÔÇÖs thought in ethics, of any help to justify the development and innovation concerning Digital Rupiah in Islamic economy and Islamic economics? This method of this research is a comparative analysis for which case seeking similarities and differences among some CBDC. The result is any potential harm of Digital Rupiah to Islamic economy by which case it relies on the way we understand interest, usury and underlying assets. SidgwickÔÇÖs account of rational benevolence and universal happiness could be a good framework for justifying Digital Rupiah in Islamic economy┬á┬á